Sinergi Difusi Inovasi dan Partisipasi dalam Ekosistem Komunikasi Digital UMKM Pengrajin Setu Tangerang Selatan - Gadis Octory; Udi Rusadi; Jamalullail (Communicology: Jurnal Ilmu Komunikasi, 2025)
The digital transformation of creative MSMEs requires a communication approach that integrates innovation diffusion with community participation. However, previous studies often treat these domains separately, leaving limited understanding of how digital empowerment unfolds within local community contexts. This study aims to analyze the synergy between innovation diffusion and community participation within the digital communication ecosystem of creative MSMEs in Setu District, South Tangerang City. This research employs a qualitative case study design involving five key informants, consisting of three craft artisans, the Head of Setu District, and a representative of Dekranasda South Tangerang. Data were collected through semi-structured interviews, observations of mentoring activities, program documentation, and a supplementary Google Form survey. The findings indicate that digital adoption occurs through iterative cycles of exposure, experimentation, peer learning, and community validation, shaped by trust and collaborative social relations among artisans. Participation is strongest during the implementation and evaluation stages through hybrid communication combining face-to-face interaction and WhatsApp-based micro-learning.Using the SKIP Analytical Framework (Synergy of Innovation and Participation), this study demonstrates how innovation and participation mutually reinforce digital empowerment within the local creative ecosystem, resulting in a more convergent, adaptive, and sustainable model of community-based development communication.